2012
DOI: 10.1007/s00436-012-3158-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the impact of biosynthesized silver nanoparticles (AgNPs) in relation to malaria and filariasis vector control against Anopheles stephensi Liston and Culex quinquefasciatus Say (Diptera: Culicidae)

Abstract: Biosynthesized nanoparticles have been achieved using environmentally acceptable plant extract and eco-friendly reducing and capping agents. The present study was based on assessments of the larvicidal activities to determine the efficacies of synthesized silver nanoparticles (AgNPs) using aqueous leaf extract of Vinca rosea (L.) (Apocynaceae) against the larvae of malaria vector Anopheles stephensi Liston and filariasis vector Culex quinquefasciatus Say (Diptera: Culicidae). Larvae were exposed to varying con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 40 publications
1
35
0
1
Order By: Relevance
“…stephensi Liston and filariasis vector Cx. quinquefasciatus Say (Diptera: Culicidae) have been determined (Subarani et al 2013). In their larvicidal activity test, the results showed that the maximum efficacy has been observed in synthesized AgNPs against the fourth instar larvae of An.…”
Section: Discussionmentioning
confidence: 92%
“…stephensi Liston and filariasis vector Cx. quinquefasciatus Say (Diptera: Culicidae) have been determined (Subarani et al 2013). In their larvicidal activity test, the results showed that the maximum efficacy has been observed in synthesized AgNPs against the fourth instar larvae of An.…”
Section: Discussionmentioning
confidence: 92%
“…In the presence of Asiatic Pennywort and Bryophyllum leaf extracts, the formation of Ag°nanoparticles was wrongly assigned by XRD technique, and the presence of AgCl nanoparticles was ignored (Saikia et al 2015). Subarani et al (2013) reported the formation of Ag o nanoparticles from Vinca rosea (L.) (Catharanthus roseus); however, some silver oxides probably contaminated nanostructure, as revealed by XRD analysis. The Opuntia ficus-indica produced both Ag o nanoparticles and AgCl nanoparticles (Gade et al 2010).…”
Section: Plantsmentioning
confidence: 97%
“…Essential oils obtained from aromatic plants like Eucalyptus (E. sideroxylon, E.globulus ssp globulus, and E. globulus ssp maidenii) were good and safe alternatives due to their low toxicity to mammals and easy biodegradability with knockdown time 50 % (KT 50 ) values of 24.75, 27.73, and 31.39 min (Toloza et al 2010). Subarani et al (2013) reported that the Vinca rosea-synthesized silver nanoparticles did not exhibit any noticeable toxicity on Poecilia reticulata after 24, 48, and 72 h of exposure. These results suggest that the synthesized AgNPs have the potential to be used as an ideal eco-friendly approach for the control of the Ae.…”
Section: Discussionmentioning
confidence: 99%